Digital Source Criticism: Evaluating YouTube as Historical Evidence of Javanese Traditional Wedding Ceremonies - Siregar, Jenny Sista; Josua, Dian Pertiwi (Diakronika, 2025)
This article criticism from internal and external sources on digital historical evidence in the form of YouTube videos. These videos complement printed historical evidence, including manuscripts, magazines, contemporary newspapers, and paintings, on Javanese traditional wedding ceremony traditions, especially those of the Yogyakarta and Surakarta Kratons. The research method employs the historical method, which includes heuristics, source criticism, interpretation, and historiography. It primarily focuses on digital historical source criticism and is conducted through documentation studies utilizing YouTube and thematic coding analysis. This analysis is applied to data on traditional wedding ceremonies performed outside palace walls by government officials of the Republic of Indonesia at their children's weddings. The study's results show: (a) Difficulty in finding printed sources can be supplemented with digital historical sources, such as YouTube videos covering Javanese traditional wedding ceremonies. (b) Internal criticism encompasses evaluating the suitability of the event's broadcast time and date, the appropriateness of the title and content in photos, videos, or text, the validity and authenticity of the archives, and the video's purpose. (c) External criticism involves assessing the creator's account credibility, witnesses, sources, and reference materials in the videos. Videos are stored as historical evidence using links and metadata, including keyword specifications, synonyms, video title, channel name, and publication date, so the same video can be found again